The effect of isolated soy protein adjunctive with flaxseed oil on markers of inflammation, oxidative stress, acute phase proteins, and wound healing of burn patients; a randomized clinical trial. Issue 1 (February 2018) - Babajafari, Siavash; Akhlaghi, Masoumeh; Mazloomi, Seyed Mohammad; Ayaz, Mehdi; Noorafshan, Ali; Jafari, Peyman; Hojhabrimanesh, Abdollah
Highlights: Nutritional support is the most significant aspects of care for burn patients. To the best of our knowledge, no human study has examined the wound-healing effect of isolated soy protein and flaxseed oil in buirn patients. Isolated soy protein and flaxseed oil attenuated inflammation and oxidative stress in burn patients. Stereological assay indicated higher wound healing in burn patients. Abstract: Introduction: The objective was to determine the effect of isolated soy protein (ISP) and flaxseed oil (FO) on inflammatory and oxidative stress indices, acute phase proteins, and wound healing of burn patients. Methods: One hundred eighty-eight patients were assessed for eligibility in this randomized controlled trial. Of these, seventy-three eligible patients (total burn surface area 20–50%) were randomly assigned to 3 isocaloric groups, labeled as control (wheat flour + corn oil (CO)), ISP + FO, and ISP + CO, to receive these nutrients for 3 weeks. We used intention to treat analysis to overcome bias. Because of the large perturbation in water compartments, patients received nutrients from 4th to 25th day of admission. Serum high sensitivity C-reactive protein (hs-CRP), malondialdehyde (MDA), superoxide dismutase (SOD), ferritin, albumin, and transferrin were measured. The wound area was evaluated by stereological test. Results: During the 3-week intervention, hs-CRP (−19.4 ± 5.6, −11.7 ± 4.7 μg/ml) and ferritin (−83.8 ± 20.5, −80.1 ± 19.6 ng/ml) levels changes significantly reduced compared to the control group (P < 0.05). MDA level (−0.05 ± 0.21 μmol/l) significantly decreased in group A (P < 0/05) but was not significant in groups B and control (P > 0.05). Albumin level (0.59 ± 0.14, 0.30 ± 0.12 g/dl) significantly increased in group A compared to the control group (P < 0.05), but no significant relationship was found between other groups (P > 0.05). Transferrin level (4.9 ± 3.6, 2.9 ± 5.1 g/dl) significantly increased in ISP groups compared to the control (P < 0.05). SOD improved in all groups with no significant difference between them (P > 0.05). The stereology examination showed significant improvement in wound healing in the ISP groups on days 22 and 25 compared to the control group. Conclusion: Nutritional supplements with ISP may attenuate post-burn oxidative stress and inflammation, leading to improved wound healing in burn patients. Flaxseed oil may not exert a beneficial effect over the ISP.